Ethanolic extract of Dayak onion (Eleutherine palmifolia) prevented sperm membran damage in mice exposed to monosodium glutamate - Syahraini Adhiya Lathifah; Aldin Akbar Rahmatullah; Boedi Setiawan; Chairul Anwar Nidom; Nove Hidajati; Sri Mulyati; Tri Wahyu Suprayogi (Universitas Airlangga, 2024)
Monosodium glutamate (MSG) could cause increased production of reactive oxygen species (ROS), causing oxidative stress in the testicles, which adversely affected sperm quality. Dayak onion extract which is known for its high antioxidant content, could help alleviate oxidative stress caused by MSG. This research examined the effect of Dayak onion (Eleutherine palmifolia) on sperm abnormalities and plasma membrane integrity in mice (Mus musculus) exposed to MSG. Twenty-five male mice, 8 weeks old with a body weight approximately 20g, were divided into five groups, C– (received 0.5% Na-CMC), C+ (received 4 mg/g bw MSG), and three treatment groups (T1, T2, T3) which were given 4 mg/g bw MSG accompanied by Dayak onion extract at doses of 30, 60, and 120 mg/kg bw respectively. All treatments lasted for 52 days. Significant differences (p <0.05) in sperm abnormalities and plasma membrane integrity were observed among the groups. Sperm abnormalities found were (12.3 ± 1.92), (61.1 ± 3.10), (41.6 ± 2.87), (30.4± 1.91), and (18.2 ± 2.10) % respectively for C–, C+, T1, T2 and T3. Meanwhile, sperm plasma membrane integrity found were (33.0 ± 3.24), (69.3 ± 2.32), (41.8 ± 2.42), (55.4 ± 3.11), and (64.2 ± 1.27) % respectively for C–, C+, T1, T2 and T3. These results indicate that Dayak onion extract could help reduce sperm abnormalities and maintain plasma membrane integrity in mice exposed to MSG.